Slow flow induces endothelial dysfunction by regulating thioredoxin-interacting protein-mediated oxidative metabolism and vascular inflammation - Wang, Yongshun; Liu, Jingjin; Liu, Huadong; Sun, Xin; Chen, Ruimian; Liao, Bihong; Zeng, Xiaoyi; Zhang, Xiaoxin; Dong, Shaohong; Xia, Zhengyuan; Yuan, Jie (Frontiers in Cardiovascular Medicine, 2022)
Endothelial cells are highly sensitive to hemodynamic shear stresses, which act in the blood flow’s direction on the blood vessel’s luminal surface. Thus, endothelial cells on that surface are exposed to various physiological and pathological stimuli, such as disturbed flow-induced shear stress, which may exert effects on adaptive vascular diameter or structural wall remodeling. Here we showed that plasma thioredoxin-interactive protein (TXNIP) and malondialdehyde levels were significantly increased in patients with slow coronary flow. In addition, human endothelial cells exposed to disturbed flow exhibited increased levels of TXNIP in vitro. On the other hand, deletion of human endothelial TXNIP increased capillary formation, nitric oxide production and mitochondrial function, as well as lessened oxidative stress response and endothelial cell inflammation. Additional beneficial impacts from TXNIP deletion were also seen in a glucose utilization study, as reflected by augmented glucose uptake, lactate secretion and extracellular acidification rate. Taken together, our results suggested that TXNIP is a key component involved in mediating shear stress-induced inflammation, energy homeostasis, and glucose utilization, and that TXNIP may serve as a potentially novel endothelial dysfunction regulator.